2020
DOI: 10.21270/archi.v9i4.5031
|View full text |Cite
|
Sign up to set email alerts
|

Recomendações em cirurgias bucomaxilofaciais de urgência e emergência em tempos de COVID-19

Abstract: Embora as rotas de transmissão da COVID-19 ainda não estejam totalmente identificadas, a transmissão homem-a-homem já é uma realidade em muitos países. Este trabalho tem por objetivo reunir recomendações dos órgãos de saúde e de estudos em artigos científicos relacionadas a condutas especiais do cirurgião bucomaxilofacial no período perioperatório de urgência e emergência. A justificativa é a possibilidade de infecção cruzada por meio da inalação de partículas produzidas durante os procedimentos cirúrgicos. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…Similar findings were reported in previous studies that assessed the impact of the COVID‐19 pandemic on IRD patients 18,19 . However, some literature reported a relative male predominance among IRD patients with severe SARS‐CoV‐2 infection 20,21 …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar findings were reported in previous studies that assessed the impact of the COVID‐19 pandemic on IRD patients 18,19 . However, some literature reported a relative male predominance among IRD patients with severe SARS‐CoV‐2 infection 20,21 …”
Section: Discussionsupporting
confidence: 86%
“…18,19 However, some literature reported a relative male predominance among IRD patients with severe SARS-CoV-2 infection. 20,21 As reported by the Jaber Hospital electronic medical registry, the total number of hospitalized patients with COVID-19 in the same time period as our data collection was 13 825. A recent comparative study 22 revealed that, compared with matched comparators, IRD patients had a higher risk of hospitalization (relative risk [RR] = 1.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…33,34 Due to the depletion of B cells and diminished viral clearance, long-term rituximab therapy may result in decreased antibody formation, which might interfere with the antibody responses to inhibit viral reproduction. 35,36 Depending on the type of biological agents they receive, IRD patients may have a variable risk of poor clinical outcomes, an in-…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, B cells play an essential role in the early antiviral response, even though the innate immune system and T cells are of utmost importance 33,34 . Due to the depletion of B cells and diminished viral clearance, long‐term rituximab therapy may result in decreased antibody formation, which might interfere with the antibody responses to inhibit viral reproduction 35,36 …”
Section: Discussionmentioning
confidence: 99%